MODERN TECHNICAL DEVICES IN CRIME DETECTION - Makhmudjonov Qilichbek Dilshod Ogli (Scholar Express Journals, 2024)
In this article, the concepts of crime and criminalistics, which are increasingly relevant in today's world, are highlighted. It explores the diverse range of modern technical devices used in crime detection, offering an indepth look at their types, advantages, and practical applications. By examining technologies such as DNA sequencing, biometric identification, and cyber forensics, the article demonstrates how these innovations enhance the efficiency and accuracy of criminal investigations. Additionally, the article discusses the convenience and effectiveness of these tools in identifying, predicting, and preventing criminal activities. Through a comprehensive analysis, the article underscores the transformative impact of modern technology on crime detection, contributing to a more effective and just criminal justice system.
Keywords: crime; biometric identification; criminalistics; technical means